Commensal borings from the Middle Devonian of central New York: ecologic and taxonomic review of Clionoides, Clionolithes, and Canaliparva n. ichnogen. (January 2014) - Furlong, Carolyn M.; McRoberts, Christopher A.
Abstract : The examination of 730 borings within 88 brachiopod hosts form the Middle Devonian of central New York State revealed four ichnospecies belonging to three ichnogenera that have taxonomic histories riddled with confusion, controversy and contradiction. New observations of the ichnotaxa question long-held views of a simple morphologic differentiation between sponge borings and worm borings. Clionoides Fenton and Fenton, 1932 is here considered a sponge boring, which is comprised of a complex, multi-dimensional system of tunnels, shafts, canals, microterraced bowl-shaped structures and cone extensions, and is a senior synonym of Paleosabella (McCoy 1855) and Vermiforichnus Cameron, 1969a. Clionolithes Clarke, 1908 is a sponge boring possessing a rosette, branching network extending from a central node and is a senior synonym of Nododendrina Vogel et al., 1987 and Ramodendrina Vogel et al., 1987. The creation of Canaliparva circularis n. ichnogen. n. ichnosp. is needed to accommodate simple, vertically oriented, U-shaped tunnels that are indicative of worm activity. Paleoecologic evidence supports a commensal relationship between the endoliths and hosts based upon boring site frequencies in the hosts, boring patterns and five inter-specific co-occurrences between traces. These new data suggest greater diversity and ecologic complexity in ichnofaunal paleocommunities from the Middle Devonian than previously recognized.